2015
DOI: 10.1186/s12887-015-0397-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of caregiver depression and family functioning after perinatal stroke

Abstract: BackgroundPerinatal stroke is a leading cause of cerebral palsy and lifelong neurological morbidity. Studies on perinatal stroke outcomes are increasing, although examinations of its broader impact on parents and families have been limited. A recent study found that parents of children with moderate and severe outcomes have increased risk for psychosocial concerns, including depressive symptoms and poor family functioning. Other parents adapt remarkably well, but how this occurs is unknown. The primary aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 64 publications
0
29
0
9
Order By: Relevance
“…Parents mentioned the strong sense of guilt and self-blame experienced after a diagnosis of perinatal stroke – a recognised problem [74, 75]:… you blame yourself and then you, you think that everyone else is blaming you as well. – Mother, Focus group 1…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents mentioned the strong sense of guilt and self-blame experienced after a diagnosis of perinatal stroke – a recognised problem [74, 75]:… you blame yourself and then you, you think that everyone else is blaming you as well. – Mother, Focus group 1…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, following a diagnosis of perinatal stroke, families experience a range of emotions including feelings of guilt and self-blame [74, 75]. There is also uncertainty about the future in terms of the nature and severity of difficulties their child may face.…”
Section: Discussionmentioning
confidence: 99%
“…early diagnosis, positive attributes of the physician, informative content) has been linked with better adaptation . Failure to promptly identify and support parental psychosocial issues may contribute to mental health morbidity for the family of the child with CP …”
mentioning
confidence: 99%
“…Human is a social being and to meet the different daily needs, and sharing feeling, it is necessary to meet other people in our in around. Likewise, it is also reported in a study [17] that social support had strong correlation with quality of life outcomes in caregivers. Study found that availability of sub-caregivers at home to help in care of survivors is a true predictor of quality of life and satisfaction to health among caregivers.…”
Section: Discussionmentioning
confidence: 87%